Tracing Progressive Currents in Indonesian Islam and Christianity: Social Justice, Modernity, and Gender Equality - Nursyabani, Mirza (UIN Sunan Kalijaga Yogyakarta, 2024)
This paper argues that Western Progressives influenced religious views influenced religious outlooks of both Islam and Christianity in Indonesia, despite their selective and adaptive attitude. In support of this argument, the article has looked at the parallel between Progressive and both religions by discussing the most common themes advanced by progressive religions as illustrated in the following four points: (1) progressive figures or organizations in Indonesia (2) social justice and religious freedom within Pancasila (3) the link between religion and modernity (4) gender equality. It is argued that the previous four points are fundamental issues that imply unfamiliar religious views that reflect their respective tenets. It is important to realize that this paper does not imply that the majority of Muslims and Indonesia are progressive. Nor does this paper want to judge whether progressive ideas are favorable or hurtful to the religion itself. Instead, this paper only tries to display one of the reflective sides of religions in Indonesia and leaves it to readers to assess this current development. Keywords: Progressive, Islam, Christianity, Indonesia